Audience Interbrain Synchrony During Live Music Is Shaped by Both the Number of People Sharing Pleasure and the Strength of This Pleasure - Chabin, Thibault; Gabriel, Damien; Comte, Alexandre; Pazart, Lionel (Frontiers in Human Neuroscience, 2022)
The study of interbrain coupling in a group of people attending a concert together is a favourable framework to estimate group emotions and more precisely emotional connection between people sharing situations in the same environment. It offers the advantage of studying interactions at the group level. By recording the cerebral activity of people from an audience during a concert using electroencephalography, we previously demonstrated that the higher the emotions and the physically closer the people were, the more the interbrain synchrony was enhanced. To further investigate the parameters that shaped inter-brain synchronization in this context, we now focus on the emotional dynamics of the group as a whole by identifying specific moments in the concert that evoked strong or weak emotions, as well as strong or weak emotional cohesion between individuals. We demonstrated that audience interbrain synchrony is mainly driven by the strength of felt and that the group emotional cohesion can enhance IBS, but is not sufficient to shape it.